2004
DOI: 10.1074/jbc.m311864200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Hydroxyproline (Hyp)-Arabinogalactan Polysaccharide from Repetitive Ala-Hyp Expressed in Transgenic Nicotiana tabacum

Abstract: A synthetic gene encoding the fusion protein (AlaHyp) 51 -enhanced green fluorescent protein expressed in Nicotiana tabacum cells produced a fusion glycoprotein with all proline residues hydroxylated and substituted with an arabinogalactan polysaccharide. Alkaline hydrolysis of the fusion glycoprotein yielded a population of hydroxyproline (Hyp)-arabinogalactan polysaccharides ranging in size from 13 to 26 saccharide residues/Hyp, with a median size of 15-17 residues. We isolated a 15-residue Hyp-arabinogalact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
150
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 55 publications
9
150
0
1
Order By: Relevance
“…4), we propose that the two enzymes transfer Fuc residues onto two different Ara residues on AGP molecules (enzyme specificity dictated by the fucosylation sites). Tan et al (32) have shown that the expression of a synthetic gene encoding an [Ala-Hyp] 51 peptide in tobacco BY2 cells produced and secreted a mixture of glycoproteins having Hyp residues substituted with arabinogalactan (AG) polysaccharides (DP13-26) and containing terminal Ara residues ␣(1,3)-or ␣(1,5)-linked. A simplified presentation of this AG polysaccharide structure is depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), we propose that the two enzymes transfer Fuc residues onto two different Ara residues on AGP molecules (enzyme specificity dictated by the fucosylation sites). Tan et al (32) have shown that the expression of a synthetic gene encoding an [Ala-Hyp] 51 peptide in tobacco BY2 cells produced and secreted a mixture of glycoproteins having Hyp residues substituted with arabinogalactan (AG) polysaccharides (DP13-26) and containing terminal Ara residues ␣(1,3)-or ␣(1,5)-linked. A simplified presentation of this AG polysaccharide structure is depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…BY2 cells were chosen as the expression system for two reasons: (i) tobacco BY2 and Arabidopsis suspension cells produce similar AGPs (32), and (ii) AGPs in both BY2 and Arabidopsis suspension cells lack Fuc (32), making them ideal substrates for AGP-FUTs.…”
Section: ␣(12)futs Specific To Arabinogalactan Proteinsmentioning
confidence: 99%
“…These spheroidal nanoparticles are concentrated during evaporation, and the highly structural flexibility of the protein backbone as well as the anchored bulky AG branches of the AGPs allow these macromolecules to be tightly packed (29), reaching an intimate connection between adjacent nanoparticles. Subsequent Ca 2+ -driven cross-linking among carboxyl groups of the uronic acid residues within the AGPs and the pectic acids in the extracellular space favors the cohesion of the adjacent AGP-rich nanoparticles, gives rise to the generation of an adhesive film (24,31,38), further aids in the curing progress of the exuded adhesive, and eventually realizes the adhesive function at the interface by restraining the relative movement of the adventitious roots and the corresponding substrates. Throughout these procedures, the AGP-rich ivy nanoparticles also possess the capacity to permeate irregularities present on the substrates owing to their rough surfaces in most cases, resulting in a strong mechanical interlocking at the interface and further ensuring an ideal adhesive action (26,39,40,(42)(43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…3A) (24,28,30,32,38). It has been demonstrated that numerous AGP molecules possess negative surface charge that is thought to be associated with the presence of uronic acid substituents (i.e., GlcA and GalA) at the termini of type II AGs (24,29,30).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4]35) In the present study, we used exo-β-(1→3)-galactanase to analyze specifically the distribution of L-Ara residues along the β-(1→6)-galactan side chains and their acidic derivatives capped with 4-MeGlcA. This yielded a variety of L-arabino-galactooligosaccharides, which are usually difficult to prepare by chemical degradation due to the acid-sensitive nature of their L-arabinofuranosidic linkages.…”
Section: Discussionmentioning
confidence: 99%